CULTIVATION OF SEAWEED Caulerpa racemosa USING DIFFERENT SUBSTRATES ON A LABORATORY SCALE - Jayusri, Jayusri; Cokrowati, Nunik; Diniarti, Nanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Caulepa racemosa is a type of sea grape from the group of green algae (Chlorophyceae) that can be found in Indonesian waters. Coastal communities use this species as a source of daily food. Besides being a food ingredient, C. racemosa can be used for medical purposes because it contains antioxidants. The distribution of C. racemosa and its density in waters depends on the type of substrate and season. The substrate in the cultivation container is an essential factor in cultivating C. racemosa. Various substrates have different characteristics and influence the growth of C. racemosa. This research aims to analyze the best substrate for the survival of seaweed on a laboratory scale. This research used an experimental method using a Completely Randomized Design (CRD) consisting of 4 treatments, namely different substrates of sand, coral, volcanic rock, and coral sand. The results of this research are that different types of substrates have a real influence on the survival rate of C. racemosa cultivated on a laboratory scale. Sand substrate gave the best results: a survival rate of 112.83%, a final weight of 22.56 g, and the highest antioxidant content on volcanic rock substrate of 83.19%. This research concludes that differences in substrate directly influence the survival rate and final weight of C.racemosa. The substrate that provided the best survival rate of 112.83% was sand substrate.